Identification of Drought Tolerant Mutant Lines of TEF [ERAGROSTIS TEF (ZUCC.) TROTTER] - Blösch, Regula; Rindisbacher, Abiel; Plaza-Wüthrich Sonia; Röckel, Nora; Weichert, Annett; Cannarozzi, Gina; Tadele, Zeruhin (Afrika Focus, 2019)
Introduction: Tef [Eragrostis tef (Zucc.) Trotter] is the major food crop in Ethiopia where it is annually cultivated on about 30% of the total area allocated to cereals. The productivity of tef is, however, significantly reduced by drought which can occur at either the early or the late developmental stage of the crop. Methodology: A total of 10,000 EMS (ethyl methane sulfonate) mutagenized M2 tef populations were screened first for early and second for terminal drought tolerance. The performance of candidate lines was investigated using diverse agronomical and physiological parameters. Results and discussion: Several promising lines were obtained for both early and terminal drought tolerance. Among these, genotypes with outstanding performance were found for two drought tolerant tef lines targeting early drought tolerance (dtt2 and dtt13) and three terminal drought tolerant lines targeting terminal drought tolerance (tdt9, tdt15 and tdt19). Conclusions: Candidate lines for both early and terminal drought tolerance will play vital roles in deve- loping drought tolerance in tef improvement. KEY WORDS: DROUGHT TOLERANCE, ERAGROSTIS TEF, ORPHAN CROP, MOISTURE SCARCITY, TEF